Antimicrobial nisin acts against saliva derived multi-species biofilms without cytotoxicity to human oral cells - Shin, Jae M.; Ateia, Islam; Paulus, Jefrey R.; Liu, Hongrui; Fenno, J. Christopher; Rickard, Alexander H.; Kapila, Yvonne L. (Frontiers in Microbiology, 2015)
Objectives: Nisin is a lantibiotic widely used for the preservation of food and beverages. Recently, investigators have reported that nisin may have clinical applications for treating bacterial infections. The aim of this study was to investigate the effects of ultra pure food grade Nisin ZP (> 95% purity) on taxonomically diverse bacteria common to the human oral cavity and saliva derived multi-species oral biofilms, and to discern the toxicity of nisin against human cells relevant to the oral cavity. Methods: The MICs and MBCs of taxonomically distinct oral bacteria were determined using agar and broth dilution methods. To assess the effects of nisin on biofilms, two model systems were utilized: a static and a controlled flow microfluidic system. Biofilms were inoculated with pooled human saliva and fed filter-sterilized saliva for 20-22 h at 37°C. Nisin effects on cellular apoptosis and proliferation were evaluated using acridine orange/ethidium bromide fluorescent nuclear staining and lactate dehydrogenase activity assays. Results: Nisin inhibited planktonic growth of oral bacteria at low concentrations (2.5 – 50 μg/ml). Nisin also retarded development of multi-species biofilms at concentrations ≥ 1 μg/ml. Specifically, under biofilm model conditions, nisin interfered with biofilm development and reduced biofilm biomass and thickness in a dose-dependent manner. The treatment of pre-formed biofilms with nisin resulted in dose- and time-dependent disruption of the biofilm architecture along with decreased bacterial viability. Human cells relevant to the oral cavity were unaffected by the treatment of nisin at anti-biofilm concentrations and showed no signs of apoptotic changes unless treated with much higher concentrations (> 200 μg/ml). Conclusions: This work highlights the potential therapeutic value of high purity food grade nisin to inhibit the growth of oral bacteria and the development of biofilms relevant to oral diseases.